2020
DOI: 10.3390/cancers12071909
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of KIF14, Mieap, and EZR in a New Type of the Invasive Component, Torpedo-Like Structures, Predetermines the Metastatic Potential of Breast Cancer

Abstract: Intratumor morphological heterogeneity reflects patterns of invasive growth and is an indicator of the metastatic potential of breast cancer. In this study, we used this heterogeneity to identify molecules associated with breast cancer invasion and metastasis. The gene expression microarray data were used to identify genes differentially expressed between solid, trabecular, and other morphological arrangements of tumor cells. Immunohistochemistry was applied to evaluate the association of the selected proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…4). 198,199 Tubular and alveolar structures are transcriptionally similar and demonstrate a similar expression of epithelial and mesenchymal markers. Solid structures show an increase in mesenchymal traits but retain epithelial features.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…4). 198,199 Tubular and alveolar structures are transcriptionally similar and demonstrate a similar expression of epithelial and mesenchymal markers. Solid structures show an increase in mesenchymal traits but retain epithelial features.…”
Section: Cancermentioning
confidence: 99%
“…202 Distant metastases are also frequently detected in breast cancers with single tumour cells with epithelial-like morphology, 203 and in breast cancers that express kinesin-14 (KIF14) and mitochondria-eating protein (Mieap), but lack ezrin (EZR) at the tips of torpedo-like structures. 199 The nature of torpedo-like structures, e.g., their EMT features, remains to be elucidated; however, KIF14, Mieap and EZR proteins are known to be important regulators of tumour cell migration and invasion. [204][205][206] Based on all these results, we assumed that tubular and alveolar structures show decreased invasive potential, whereas solid, trabecular and torpedo-like structures, as well as small groups of tumour cells and single tumour cells, are highly invasive.…”
Section: Cancermentioning
confidence: 99%
“…KIF14 (Kinesin Family Member 14) is a prognostic predictor of BC 53 , 54 , 70 . It promotes AKT phosphorylation and contributes to chemoresistance in triple-negative breast cancers 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…6B-E ) results demonstrated that knockdown of SOCS1 reduced SOCS1 expression in HTR8+ siSOCS1 group compared with that in the HTR + NC group, but IFN-γ intervention increased SOCS1 expression in HTR8 + IFN-γ + siSOCS1 group compared with that in the HTR + siSOCS1 group. Compared with the siNC group, western blot analysis indicated that EZR and PDGFRA expressions, which is related to cell invasion and migration respectively ( 19 , 20 ), were reduced in the siSOCS1 group; whilst the expression of cell apoptosis marker cleaved caspase3 was increased in the siSOCS1 group ( Fig. 6B and C ).…”
Section: Resultsmentioning
confidence: 94%